Microwave Attenuation Studies of Polypyrrole-SWCNT Nanocomposite Films for Improved EMI Shielding. (1st September 2022) - Raju, P.; Kanaka Durga, M.; Udaya Kumar, S.; Neeraja Rani, G.
Abstract : In the process of finding stable, lightweight, broadband, cost-effective and improved electromagnetic interference (EMI) shielding material, electromagnetic wave attenuation properties of polypyrrole (PPy)—single-walled carbon nanotube (SWCNT) nanocomposite hybrid films were investigated in X-band region (8.2–12.4 GHz) and reported in the present work. The incorporation of SWCNT as a nanofiller in polymer matrix exhibits enhanced EMI shielding performance as compared to pure polymer films. The substantial values of dielectric loss with good impedance matching contribute to improvement in EMI shielding performance. It is found that with an increase of SWCNT loading in polymer matrix from 0 wt% to 5 wt%, nanocomposite films display a gradual increase in AC conductivity and total shielding effectiveness. The maximum total shielding effectiveness of 32.10 dB and minimum reflection loss of −45.54 dB with a wide bandwidth of 3.1 GHz, were obtained for 5 wt% CNT loading. The present results revealed that the prepared nanocomposite films are appropriate materials for lightweight, broadband EMI shields for radar and stealth applications.